(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
Nowadays mafias are seeing a phase of strong expansion, in a variety of different directions and shapes. The work carried out by the General States promoted by the Ministry of Justice has highlighted the complexity of the relations between mafia and society and underlined the weak areas of the existing law. The legal system is now facing the necessity of developing new strategies and tools for tackling and preventing the mafia phenomenon which increasingly proves to have no borders, either geographically or socially or culturally. Keywords: organized crime, mafias, General States , strategy, prevention, awareness, legality